OPTIMALISASI KUNJUNGAN POSYANDU BALITA MELALUI KELAS IBU BALITA DI WILAYAH KERJA PUSKESMAS PEGAMBIRAN KELURAHAN GATES NAN XX KOTA PADANG - Desmawati Desmawati; Meilinda Agus; Agnestya Nurul Fergita; Mimi Rahmawati; Nissa Primasari; Syifa Fadhilah; Trisnanda Marintan (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
The Integrated Service Post (Pos Pelayanan Terpadu/Posyandu) closely monitors children's growth and development through routine weighing to detect any growth and development disorders early. Classes are provided for mothers to discuss health services, nutrition, and growth and development, facilitated by trained personnel using Maternal and Child Health (MCH) books. We aim to raise awareness among the people of RT 01 RW 01, Gates Nan XX sub-district, about the importance of monitoring the growth and development of babies and toddlers. Using the USG scoring method, an analytical survey was conducted to identify community issues and establish priorities. Classroom interventions were performed for mothers of toddlers using MCH and Audio-Visual media, and activities were evaluated for effectiveness. Results of the health data collection that the service team carried out previously at Gates Nan XX Village showed that the number of babies aged 29 days-12 months was two people with a history of weighing every three months, one person (50%), while the population of toddlers aged 1-5 years is nine people, with a history of not having been weighed in the last three months as many as seven people (78%). After the intervention of mother empowerment through the toddler mother class, it is obtained that the mothers of toddlers are committed to monitoring the growth and development of toddlers at the posyandu and actively participating in the class of mothers of toddlers actively participate in attending toddler mother classes.